La cultura en un mundo global: ¿uniformización o diversificación? (2020)
This paper discusses the cultural changes brought about by the globalization processes by reviewing the homogenization-diversification dilemma that has dominated the debate in this field. To this end, the article examines the transformations that the expansion of the global capitalism has brought about in cultural frameworks, representations, and forms of symbolic consumption. The positions that argue that we are facing a process of cultural diversification thanks to the intensive exchange of messages and the flows of people will be reviewed, as well as those that state that the concentration of the production and distribution of symbolic goods in large corporations impoverishes imaginaries and reduces the richness of cultural frameworks. The intention of this reflection is to identify the limits of this disjunctive to move forward to more complex interpretative models, in accordance with the heterogeneity of the phenomena that are underway in the contemporary world.